2013
DOI: 10.1177/0363546513503812
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Radiographic Comparison of Arthroscopic Suprapectoral and Open Subpectoral Biceps Tenodesis Sites

Abstract: This anatomic study provides new information on tunnel placement in 2 biceps tenodesis techniques. In addition, it provides clinically relevant anatomic and radiographic guidelines using clinically pertinent landmarks. This information may be useful in preoperative planning, intraoperative technique, and postoperative assessment of both open subpectoral and arthroscopic suprapectoral biceps tenodesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 14 publications
2
44
0
1
Order By: Relevance
“…20,31 Our data indicate an average difference in location between techniques of 2.74 cm, which was statistically significant. This is similar to the findings of Johannsen et al, 9 who recently reported that the open subpectoral approach placed the tenodesis tunnel on average 2.2 cm further distal than the arthroscopic suprapectoral approach.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…20,31 Our data indicate an average difference in location between techniques of 2.74 cm, which was statistically significant. This is similar to the findings of Johannsen et al, 9 who recently reported that the open subpectoral approach placed the tenodesis tunnel on average 2.2 cm further distal than the arthroscopic suprapectoral approach.…”
Section: Discussionsupporting
confidence: 91%
“…2 Numerous options for surgical approach, location, and method of fixation have been investigated for biceps tenodesis in both cadaveric and clinical studies. Long head biceps tenodesis can be performed with an open [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or arthroscopic technique 9,18-33 and can be positioned high at the entrance of the bicipital groove, in the suprapectoral location just proximal to the pectoralis major tendon, 9,16,22,30,31,34 in a subpectoral location at or distal to the pectoralis major tendon, 6,10,12,15,16,34 or in other positions, including the conjoint tendon or soft tissue tenodesis sites. 27,32,33,35 Arthroscopic suprapectoral and open subpectoral techniques are 2 common distal techniques for biceps tenodesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Subpectoral fixation has been initially described [33] to reduce the rate of postoperative pain traditionally associated with arthroscopic techniques [34]. This seems related to the more distal tenodesis site achievable with subpectoral tenodesis [35]. Unfortunately, a variable spectrum of complications has been described including failure or re-rupture of the tendon, hematoma, infection, persistent pain, reaction to a fixation device, nerve injury, cosmetic deformity, and fracture [36,37].…”
Section: Discussionmentioning
confidence: 99%